People, Politics and Change : Building Communication Capacity for Governance Reform - Cabañero-Verzosa, Cecilia; Garcia, Helen R. (World Bank, Washington, DC, 2014)
The Communication for Governance and Accountability Program (CommGAP) was established in 2006 as a global program to confront challenges which create barriers to achieving effective and sustainable governance outcomes. In particular, CommGAP was created to address specific c gaps that undercut the quality of governance reform efforts: a structural gap, a process gap, and a capacity gap. The structural gap, produced by the insufficient recognition of the public sphere as an essential part in securing good governance and accountability, leads to a narrow, fragmented approach in the design and approach of many governance reform programs. The process gap is one that arises from a lack of applicable processes to deal effectively with political economy issues and people-related challenges due to vested interests and stakeholder resistance to change. The capacity gap deals with the problem of the meager capabilities among researchers, development and communication practitioners in government agencies, NGOs or private firms in ways that hinder their ability to provide effective and strategic support in the implementation of governance reform programs.